MENGEMBANGKAN KOGNISI ANAK USIA DINI MELALUI PEMBELAJARAN KOMPUTER (Studi kasus di TK Islam Makarima Kartasura Sukoharjo) - Sufa, Feri Faila (UNIVERSITAS SLAMET RIYADI, 2015)
One of the efforts in early childhood education is to improve the cognitive abilities of children. Inthe pre-observation, at the early learning, children are still unable to consistently follow the rulesof the classl and can not stay calm for a moment in the classroom because basically they likegames. The purpose of this observation is to develop the cognition of the children through themedium of learning computers. The subject of this observation were 22 students of childrengroup’s A of TK Islam Makarima. The results of the observation shows that through the study ofcomputers childre develop their cognitive abilities.Keywords: Computer Learning, Cognition, early childhood education